Underground Gun Markets - Anthony A. Braga
This paper provides an economic analysis of underground gun markets drawing on interviews with gang members, gun dealers, professional thieves, prostitutes, police, public school security guards and teens in the city of Chicago, complemented by results from government surveys of recent arrestees in 22 cities plus administrative data for suicides, homicides, robberies, arrests and confiscated crime guns. We find evidence of considerable frictions in the underground market for guns in Chicago. We argue that these frictions are due primarily to the fact that the underground gun market is both illegal and %u201Cthin%u201D -- the number of buyers, sellers and total transactions is small and relevant information is scarce. Gangs can help overcome these market frictions, but the gang%u2019s economic interests cause gang leaders to limit supply primarily to gang members, and even then transactions are usually loans or rentals with strings attached.